Using Artificial Intelligence to Identify Emotional Neglect and Manage Emotional Well-Being: A New Perspective on Enhancing Mental Health - Sneha; Sangeeta Kakkar (International Journal of Behavioral Sciences, 2025)
Background: The rising prevalence of mental health issues, coupled with a shortage of qualified professionals, necessitates innovative solutions, especially considering the lasting impact of childhood emotional neglect. Emotional neglect, one of the most profound forms of maltreatment, is a widespread concern that significantly affects an individual’s mental health and overall well-being in the long term. Aim: The purpose of this research article is to explore the capability of artificial intelligence (AI) in enhancing emotional well-being, particularly concerning individuals who experienced emotional neglect as children. Methodology: A comprehensive review incorporated the previous twelve years' papers on numerous AI technologies, encompassing machine learning, natural language processing (NLP), and facial recognition from Google Scholar, PubMed, and the library. Findings: The results suggest that AI technologies have the potential to effectively identify signs of emotional distress, leading to more accessible, flexible care options and facilitating timely, personalized interventions. These technologies might also help lessen the stigma associated with getting mental health support, making it easier for individuals to get the assistance they need. Conclusion: Regardless of the potential benefits of AI in mental health care, numerous challenges persist, such as ethical concerns, data privacy issues, and the need for human oversight. Implication: The article emphasizes the significance of incorporating AI into mental health to improve outcomes for individuals facing emotional neglect and other mental health challenges while addressing its limitations and moral implications.
Keywords: Mental health; artificial intelligence; emotional neglect; emotional well-being; supportive interventions